Current status of endoscopic full‐thickness resection with the full‐thickness resection device. Issue 2 (29th September 2022) - Mueller, Julius; Kuellmer, Armin; Schiemer, Moritz; Thimme, Robert; Schmidt, Arthur
Abstract : Endoscopic full‐thickness resection (EFTR) using the full‐thickness resection device (FTRD) is an integral part of diagnostic and therapeutic endoscopy. Since its market launch in Europe in 2014, its safety and effectiveness have been proven in numerous studies. Adaptations in design as well as new techniques, such as hybrid EFTR, expand the spectrum of the FTRD system. The following review is intended to provide an overview of the clinical application and current evidence of EFTR with the FTRD system.